Sports Coaching and Talent Scouting in Indonesia - Eki Aldapit; Pasha Erik Juntara; Guntur Yulisatria; Citra Azhariat Malasari; Novalila Azni (International Conference on Science, Education, and Technology, 2021)
Sports development through national sports coaching and talent scouting could be an instrument to sports development, performance improvement, and sports management development. The result of this review literature is to understand problems within sports coaching and talent scouting in Indonesia. The research is using secondary data. The method used in collecting data is literature review, using published literature online within 2017-2021 and relevant research results. Collected data is compulated, analysed, and deduced in order to be able to give useful recommendation. Literature review results related to sports coaching and talent scouting in Indonesia portray that the sports coaching and talent scouting in Indonesia has evolved and done well in some sports. Each sports stakeholder Has very important role in sport coaching and talent scouting. Main organization and coach needs synergy in developing sport coaching and talent scouting. Coaching and talent scouting need to be done more massive in some areas included remote area as the human resource’s potency in Indonesia is promising in some sports.